Integrated thin-film rechargeable battery in a thermoelectric scavenging microsystem - Carmo, João Paulo Pereira (2009)
Thin-film solid-state rechargeable batteries are ideal power sources for microsystems applications, where a high level of integration is required. The technology and the steps involving the fabrication of such a battery are discussed in this paper. A DC reactive sputtering technique was used in the thin-films depositions. The battery uses SnO2, Li3PO4 and LiCoO2 materials in the anode, electrolyte and cathode, respectively. The application of the battery is for use in thermoelectric energy scavenging microsystems, which converts the small thermal power available in human-body. This Lithium solid-state thin-film battery is integrated in the same device as well as the ultra low-power electronics to charge battery and perform DC-DC conversion.